Comparative Analysis of Growth Performance, Morphological Development, and Physiological Condition in Three Romanian Cyprinus carpio Varieties and Koi: Implications for Aquaculture - Dana-Andreea Șerban; Cristian-Alin Barbacariu; Marian Burducea; Mihaela Ivancia; Șteofil Creangă (Life)
This study investigates the influence of internal factors on growth dynamics in four Cyprinus carpio varieties, three Romanian strains (Frăsinet, Ineu, and Podu Iloaiei) and the Koi variety. Fish were measured for total length, maximum height, and weight at four ontogenic stages, namely 7 days post-hatch, 3 months (0+), 18 months old (1+), and 36 months (2+). Weight Gain (WG), Specific Growth Rate (SGR), Relative Growth Rate (RGR), Fulton’s condition factor, and the profile index were calculated and analyzed. Results revealed significant intervariety differences in growth performance and physiological condition across life stages. At the 2+ stage, Podu Iloaiei exhibited the highest WG (849.73 ± 4.09 g), while Koi showed the lowest (403.99 ± 14.21 g). Koi demonstrated a unique growth pattern, with the highest SGR (0.18 ± 0.00% day−1) and RGR (0.98 ± 0.05 g day−1) at the 2+ stage. Fulton’s condition factor varied markedly, with Frăsinet showing the highest value at 7 days post-hatch (149.57 ± 17.485) and Koi the lowest at the 1+ stage (0.63 ± 0.011). The profile index decreased with age in all varieties, with Podu Iloaiei showing the most dramatic change from 4.22 ± 0.149 at 7 days to 2.18 ± 0.004 at 2+. These findings highlight the complex interplay between genetic and developmental factors in carp varieties, offering new insights for tailored breeding programs and aquaculture practices.